Current Diagnosis and Management of Myocarditis - Windhi Dwijanarko; Hasanah Mumpuni; Bambang Irawan (ACI (Acta Cardiologia Indonesiana), 2016)
Myocarditis is an inflammation of the myocardium. The clinical presentations of myocarditis range from nonspecific systemic symptom such as fever, myalgias, palpitations, or exertional dyspnea, to severe hemodynamic derangement and sudden death. The wide variation of clinical manifestations has made the exact incidence of myocarditis difficult to determine. The prevalence of myocarditis based on autopsy data is ranging from 2 to 42%. Myocarditis has heterogeneous clinical presentation, ranging from mild chest pain or palpitations to cardiogenic shock and life-threatening ventricular arrhythmias. The diagnosis of myocarditis requires a high initial suspicion. Non-invasive techniques, such as cardiac magnetic resonance imaging, can be useful to diagnose and monitor of disease. The endomyocardial biopsy is the gold standard for definitive diagnosis of myocarditis and can identify the etiology of myocarditis. By endomyocardial biopsy, it can direct patients who can be managed by conventional therapy or who require specific treatment based on underlying etiology, such as antiviral or intravenous immunoglobulin infusion.Keywords: myocarditis; diagnosis; management